Accessing nanotube bands via crossed electric and magnetic fields - DeGottardi, Wade (2010)
We investigate the properties of conduction electrons in single-walled armchair carbon nanotubes in the presence of mutually orthogonal electric and magnetic fields transverse to the tube's axis. We find that the fields give rise to an asymmetric dispersion in the right- and left-moving electrons along the tube as well as a band-dependent interaction. We predict that such a nanotube system would exhibit spin-band-charge separation and a band-dependant tunneling density of states. We show that in the quantum dot limit, the fields serve to completely tune the quantum states of electrons added to the nanotube. For each of the predicted effects, we provide examples and estimates that are relevant to experiment.